2019
DOI: 10.1177/0020764019866224
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related stressors of caregiving burden among different types of family caregivers of persons with schizophrenia in rural China

Abstract: Background: Little is known about the impacts of schizophrenia on different types of caregiving burden. Aim: This study aims to examine how the severity of schizophrenia, social functioning and aggressive behavior are associated with caregiving burden across different kinship types. Method: The analytic sample included 300 dyads of persons with schizophrenia and their family caregivers in Xinjin, Chengdu, China. The 10th edition of the International Classification of Diseases (ICD-10) was utilized to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 54 publications
(95 reference statements)
3
23
0
Order By: Relevance
“…This may reflect the family members' possible commitment to agricultural labor or family-operated independent businesses (the two leading occupations). Kinship, or a caregiver's role in the family, was reported to affect the caregiver's perceptions of the burden of care, but the results of previous studies were inconsistent [75]. Our results showed that the QoL of the parents of patients was lower than that of the caregivers with other family relationships, which was congruent with several studies [76,77].…”
Section: Plos Onesupporting
confidence: 88%
“…This may reflect the family members' possible commitment to agricultural labor or family-operated independent businesses (the two leading occupations). Kinship, or a caregiver's role in the family, was reported to affect the caregiver's perceptions of the burden of care, but the results of previous studies were inconsistent [75]. Our results showed that the QoL of the parents of patients was lower than that of the caregivers with other family relationships, which was congruent with several studies [76,77].…”
Section: Plos Onesupporting
confidence: 88%
“…Parents in this study, however, show no such expectation for their ill daughters. Similar findings can be found in the study by Peng et al, [ 5 ] that the caring burden may relate to kinship types of patients with schizophrenia in Chinese society. Individuals with mental illness usually have lower marriage rate, but this phenomena happened in male more than female patients due to males carrying a heavier responsibility for providing a family living, while females are asked to meet housekeeping tasks [ 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, people with mental health conditions are seldom able to fulfill their expected social roles effectively due to physical and cognitive decline caused by illness [ 2 , 3 ]. They are accordingly dependent on their family members as their primary caregivers [ 4 , 5 ]. As indicated by previous studies, living with mental illness does not prevent people from fulfilling their social, roles shaped by their cultures including gender roles [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Approximately 25% to 50% of schizophrenia patients in Western countries and 70% in Asian countries are being cared for by their families. 3,8 Studies in developing countries showed that large families take care of the patient. 9,10 Patient care is difficult and brings a heavy burden to the caregiver.…”
mentioning
confidence: 99%
“…The concept of care burden includes the physical, emotional, social, or economic difficulties experienced by the family member who cares for the patient. 6,8,11,12 The burden concept is classified into two groups as an objective burden (revenue lost, restriction of social activities, the stress in the home environment, etc) and subjective burden (emotional distress due to the disturbing behaviors of a patient or subjective distress level associated with the patient). 13,14 Since schizophrenic patient care is a very stressful experience, the care burden negatively affects the physical and mental health and well-being of the caregiver, as well as the care process and expected patient outcome.…”
mentioning
confidence: 99%